Peran Kerja Sama Tim Dan Fasilitas Kerja Dalam Meningkatkan Motivasi Kerja Karyawan PT Asam Jawa - Purnomo, Eko; Nasution, Muhammad Irwan Padli (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Human Resources is one of the most influential factors for a company. Apart from human resources, one factor that is very influential for a company is teamwork and work facilities. Where this occurs in internships is the phenomenon of less effective communication within the team and a lack of checking the availability of office stationery such as salary card stock and HSS paper. The aim of this research is to evaluate teamwork and work facilities in increasing employee work motivation. The method used is qualitative research where data collection is carried out by observation or observation where the researcher must go directly to observe the research object and location. The importance of teamwork and employee work facilities in increasing employee work motivation at internships. Where facilities are a means to expedite and facilitate the implementation of the work process. Apart from that, teamwork is very important in a company or organization because the organization's work will not be carried out if the members of the organization or company do not work together in harmony. Therefore, the importance of teamwork between employees and superiors as well as complete facilities in an organization or company will create work comfort and work motivation in the employee. Keywords: Teamwork, Work Facilities, and Work Motivation